2005
DOI: 10.1007/s10508-005-4342-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender Identity Outcome in Female-Raised 46,XY Persons with Penile Agenesis, Cloacal Exstrophy of the Bladder, or Penile Ablation

Abstract: This review addresses the long-term gender outcome of gender assignment of persons with intersexuality and related conditions. The gender assignment to female of 46,XY newborns with severe genital abnormalities despite a presumably normal-male prenatal sex-hormone milieu is highly controversial because of variations in assumptions about the role of biological factors in gender identity formation. This article presents a literature review of gender outcome in three pertinent conditions (penile agenesis, cloacal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(86 citation statements)
references
References 84 publications
(74 reference statements)
2
80
0
4
Order By: Relevance
“…For instance, people with intersex and related conditions who have been exposed to prenatal androgen levels which are at variance to either their genotype, (male or female sex chromosomes) or their assigned birth gender are much more likely to change from the gender they were assigned at birth, than persons without these conditions [62,63,64,65]. However, although the above theory may suggest that natal females with ASD present with elevated testosterone levels, an association between high levels of testosterone in females and Gender Dysphoria have not been found.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, people with intersex and related conditions who have been exposed to prenatal androgen levels which are at variance to either their genotype, (male or female sex chromosomes) or their assigned birth gender are much more likely to change from the gender they were assigned at birth, than persons without these conditions [62,63,64,65]. However, although the above theory may suggest that natal females with ASD present with elevated testosterone levels, an association between high levels of testosterone in females and Gender Dysphoria have not been found.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 It is likely that practice has also been influenced by those cases of XY DSD who were raised as girls and who developed gender dysphoria, although other similar cases in which gender dysphoria was not encountered have received less attention. 17 The etiology of 46,XY DSD is wide ranging 18 ; although at the moment, a confirmatory genetic diagnosis is rarely sought regularly for assisting with a decision for sex assignment, it is possible that in the future ongoing technological advances will lead to a turnaround time that is so short that the knowledge of the genetic mutation may play a larger part in the sex assignment process as well as in the development of a plan for long-term surveillance. For instance, ∼20% of boys with DSD may have a mutation in the androgen receptor gene, 9 and it is possible that an early knowledge of this mutation will allow the clinician to differentiate a case of PAIS from partial gonadal dysgenesis.…”
Section: Discussionmentioning
confidence: 99%
“…with bladder exstrophy and a partly or wholly absent penis -are usually changed into girls immediately after birth. A survey showed that in adulthood only 65% of these children who were changed into girls continued to live as girls, and when individuals with gender dysphoria were excluded the figure dropped to 47% (44,45). From these examples it appears that the direct action of testosterone on the developing brain in boys and the lack of it in the developing brain in girls are crucial factors in the development of male and female gender identity and sexual orientation, although other sexually dimorphic functions still need to be investigated in these people.…”
Section: The Mechanism Of Sexual Differentiation Of the Brain: Neurobmentioning
confidence: 99%